Effect of Self-adhesive Resin Cement and Tribochemical Treatment on Bond Strength to Zirconia - Lin, Jie (Nature Publishing Group, 2010)
AIM: To evaluate the interactive effects of different self-adhesive resin cements and tribochemical treatment on bond strength to zirconia. METHODOLOGY: The following self-adhesive resin cements for bonding two zirconia blocks were evaluated: Maxcem (MA), Smartcem (SM), Rely X Unicem Aplicap (UN), Breeze (BR), Biscem (BI), Set (SE), and Clearfil SA luting (CL). The specimens were grouped according to conditioning as follows: Group 1, polishing with 600 grit polishing paper; Group 2, silica coating with 110 µm Al(2)O(3) particles which modified with silica; and, Group 3, tribochemical treatment - silica coating + silanization. Specimens were stored in distilled water at 37°C for 24 hours before testing shear bond strength. RESULTS: Silica coating and tribochemical treatment significantly increased the bond strength of the MA, UN, BR, BI, SE and CL to zirconia compared to #600 polishing. For both #600 polished and silica coating treatments, MDP-containing self-adhesive resin cement CL had the highest bond strengths to zirconia. CONCLUSION: Applying silica coating and tribochemical treatment improved the bond strength of self-adhesive resin cement to zirconia, especially for CL.